Clinical Presentation and Management of Patients With Acromegaly at a University Hospital - Leao, Felipe A (J Endocr Soc, 2021)
We conducted a retrospective analysis aiming to evaluate different treatment responses in a cohort of acromegaly patients followed at the Federal University of Minas Gerais Neuroendocrinology Outpatient Clinic who were diagnosed between the years of 1998 and 2020. Results: seventy-two patients with acromegaly were initially identified through chart review. Twelve patients were subsequently excluded from this analysis - nine patients who had been recently diagnosed and were awaiting surgical treatment as well as three patients who had been lost to follow-up. The study sample (n=60) included forty females patients (67%). Mean (range) age at diagnosis was 43.5 years-old (17-76) and mean (range) follow-up time was 107 (1-261) months. At diagnosis, 88.7% of the patients presented with a macroadenoma, and median (range) basal GH and IGF-1 of the studied population were 21.76 (0.89-193) ng/mL and 310 (110-2459) % above the age and sex-adjusted ULN, respectively. Fifty-six (93%) patients underwent transsphenoidal surgery while four patients (6.7%) received primary medical treatment. Amongst patients not cured by surgery (n=42), 37 patients (88%) were sequentially treated with first generation long-acting somatostatin analogues (SSAs) and 3 patients (7%) received cabergoline. Amongst patients sequentially treated with SSAs, 14 (38%) achieved optimal biochemical control, defined as normal age and sex-adjusted IGF-1 levels, under SSAs monotherapy (octreotide LAR maximum dose of 40 mg/28 days or lanreotide autogel maximum dose of 120 mg/28 days) while one out of three patients achieved biochemical control under cabergoline monotherapy (maximum dose of 3 mg/week). All patients who did not achieve biochemical control under SSA or cabergoline monotherapy (n=25) were sequentially treated with SSAs and cabergoline combined therapy and optimal biochemical control was achieved in 13 (52%) of them. Pegvisomant (maximum dose of 30 mg/day) was further added to the therapeutic scheme in seven patients, allowing biochemical control in 4 (57.1%) additional patients. Amongst five patients (8%) patients who were treated with adjuvant radiotherapy, two did not achieved long-term remission, despite combined therapy with SSAs, cabergoline and pegvisomant. Discussion: the high reported prevalence of macroadenomas in our cohort possibly reflects a delay in the diagnosis and may account for the low observed successful surgical rate in comparison to other series, however treatment response rates to SSAs monotherapy as well as combined SSAs and cabergoline therapy here reported are in line with previous reports. Given its low cost and larger availability, cabergolin was amply prescribed as opposed to pegvisomant, which was employed as a third-line treatment showing a disease control rate lower than previously reported in interventional studies but consistent with previous real-world data.